Characterization and calibration of MEMS inertial measurement units - Aslan, Gokcen; Saranli, Afsar (Proceedings of the ... European Signal Processing Conference (EUSIPCO), 2008)
Widening applications of inertial sensors has triggered the search for cost effective sensors and those based on MEMS technology has been gaining popularity in particular for the lower cost applications. However, inertial sensors are subject to various error sources and characteristics of these should be modelled carefully and corrective calibration performed if these sensors are to be successfully used for body state estimation and navigation. In the present paper, we review noise and deterministic error models of these sensors and consider several static and dynamic inertial sensor calibration tests. We carry out these tests to analyse the errors, derive calibration parameters and review resulting state measurement performance of a particular MEMS inertial sensor (MicroStrain 3DM-GX1) which is popularly available at reasonable cost. We present our results with the associated discussion on sensor performance.